Insights into the protein ubiquitinome in the host‒pathogen interplay during Mycobacterium tuberculosis infection - Feng, Qishun; Lin, Qiao; Huang, Guoxin; Li, Siqi; Xu, Yating; Ye, Taosheng; Zhang, Guoliang (Frontiers in Molecular Biosciences, 2025)
Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis capable of manipulating and circumventing the host’s immune system to establish infection. Ubiquitination plays a crucial role in the host’s response to pathogens; however, the global alterations in protein ubiquitination during Mtb infection remain poorly understood. To elucidate the regulatory roles of ubiquitination in the immune response to Mtb, we investigated the ubiquitome of human macrophages following Mtb infection. In our study, we identified a total of 1,618 proteins exhibiting altered ubiquitination levels, with 1,182 lysine-ubiquitination sites in 828 proteins showing increased ubiquitination and 1,077 sites in 790 proteins displaying decreased ubiquitination. Bioinformatics analyses revealed that most proteins involved in the immune response were upregulated, including those associated with autophagy, lysosome, the NF-κB signaling pathway, necroptosis, and ferroptosis. Furthermore, the ubiquitination levels of numerous proteins involved in conserved physiological processes, such as ribosome biogenesis, spliceosome function, nucleocytoplasmic transport, and mRNA surveillance, were also altered, suggesting that these pathways may be regulated by ubiquitination during Mtb infection. The extensive pool of ubiquitinated proteins and sites identified in this study will serve as a valuable resource for understanding the regulatory mechanisms of the ubiquitination system in immune responses during Mtb infection.